Ore mineralogy and host-rock geochemistry of the Cu-Rautuvaara iron oxide copper-gold deposit, Kolari, Finland - Kokko, Sini-Maaria (Helsingfors universitet, 2013)
The Cu-Rautuvaara iron-oxide copper gold (IOCG) deposit is located in the western part of the Central Lapland Greenstone belt. Cu-Rautuvaara and several other IOCG deposits are located next or within of the SSW-NNE trending Kolari-Pajala Shear Zone. Deposits are formed in the contacts of the ca. 1860 Ma Haparanda Suites monzonite-diorite intrusions and the >2050 Ma Savukoski Group supracrustal rocks. At Cu-Rautuvaara deposit Cu-Au ore is hosted by magnetite-disseminated albitite. Host rocks for the other deposits in the Kolari area are skarns and ironstones. The wall and the host rocks are hydrothermally altered. Alterations can be roughly divided to proximal and distal zones which are displaying widespread and irregular alteration zones. The distal alteration is characterized by albite ± biotite ± K-feldspar and the proximal alteration albite + magnetite ± phlogopite ± gedrite ± amphibolite ± sulphides ± clinopyroxene. Based on the mass balance calculations Zr, TiO2 and Al2O3 were immobile during the alteration. Calculations indicated that main gains for albitites were Na2O, Fe2O3, Cu and Ni. For diorites and metavolcanites gains were CaO, K2O, Ce and Ba. Albitite protolith determination by its texture and mineral assemblage is unreliable because of the intense hydrothermal alteration. Based on immobile element correlation data suggest that metavolcanites are the most preferential protolith for albitites. The main oxide in the deposits is magnetite, which locally has accessory ilmenite exsolved from it. The main sulphides are chalcopyrite, pyrite and pyrrhotite. Oxides and sulphides element contents were determined by electron microprobe analyses. Based on analyses Au occurs as native Au-Ag grains in chalcopyrite. Major trace element in pyrrhotite is Ni (0.1– 0.8 wt. %). Based on major trace elements there are two types of pyrites with Co (<3 wt. %) and Ni (<3.5 wt. %). Major trace elements in magnetites are Al2O3 (0.01 – 0.71 wt. %), V2O (<0.23 wt. %) and Cr2O3 (<0.27 wt. %). Some magnetites ...